Outer space significance in daily life in mexico city’s housing complexes (2008)
Outer space inside the housing complexes, contribute as the main core of the inhabitants coexistence. Its design has been treated just partially, using only some technical criteria, without strong bases, and without considering that life into a community is the result of social coexistence and the contact established among the housing dwellers living in the housing complex. In such sense, outer space plays a very important role and has to be linked to the urban and communal services that make life into a community possible.